2022
DOI: 10.3390/microorganisms10020478
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Novel Chlamydia trachomatis Sequence Types among Chlamydia Patients in the Republic of Belarus

Abstract: Chlamydia trachomatis (CT) is a major cause of sexually transmitted diseases worldwide. The multilocus sequence typing (MLST) of clinical samples from random heterosexual chlamydia patients who were either asymptomatic or reported clinical manifestations of genital chlamydiosis (n = 63) in each of the seven major regions of the Republic of Belarus in 2017–2018 revealed 12 different CT sequence types (STs). We found seven known STs, ST4, ST6, ST9, ST13, ST38, ST95 and ST110, and five novel variants, namely ST27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Feodorova et al (2022) in their study on random samples of heterosexual males and females in Belarus found 12 sequence types, of which seven were common, and five were new. Most of their participants were asymptomatic, whereas in the present study, aside from infertility, 65.9% of patients exhibited other symptoms, especially in the urogenital tract [24] . Also, in another study, Thapa et al (2020) reported a wide variety of sequence types in C. trachomatis isolates detected in endocervical samples of young women in Japan.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Feodorova et al (2022) in their study on random samples of heterosexual males and females in Belarus found 12 sequence types, of which seven were common, and five were new. Most of their participants were asymptomatic, whereas in the present study, aside from infertility, 65.9% of patients exhibited other symptoms, especially in the urogenital tract [24] . Also, in another study, Thapa et al (2020) reported a wide variety of sequence types in C. trachomatis isolates detected in endocervical samples of young women in Japan.…”
Section: Discussioncontrasting
confidence: 55%
“…Several MLST schemes have been developed for C. trachomatis, employing PCR amplification and DNA sequencing of five to seven specific genomic loci linked to the chlamydial genome. Among these schemes, the scheme presented by Pannekoek et al (2008) [7] , which employs seven molecular targets, has gained recognition as the preferred option for worldwide epidemiological studies and tracking the molecular evolution of C. trachomatis [24] . This MLST approach encompasses asymptomatic individuals and couples infected with either the wild type of C. trachomatis or the novel variant [8,25] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-locus sequence typing (MLST) has become a useful tool for studying the genetic diversity of important public health pathogens, leading to improvements in the monitoring and molecular epidemiology of C. trachomatis infections [ 23 , 24 ]. Several MLST-like systems able to identify LGV strains have been previously proposed, but none of them has been broadly adopted by the scientific community [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For Chlamydia spp. detection, urethral swabs, choanal cleft swabs, pharyngeal swab, and cloacal swabs from animals or human are often used for DNA extraction and testing ( Holland et al, 1990 ; Dumke et al, 2015 ; Mina et al, 2019 ; Feodorova et al, 2022 ). One route of transmission of C. psittaci is a inhalation of aerosolized bird feces from the environment ( Szeredi et al, 2005 ), and fresh feces samples from animals are also used for detection of C. psittaci ( Takashima et al, 1996 ; Sachse et al, 2012 ; McGovern et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%